Pengaruh Penerapan Model Pembelajaran Berbantuan Media Articulate Storyline terhadap Kemampuan Penalaran Matematis Siswa di SMP Negeri 1 Bone - Melisya A. Putri Kobidon; Syamsu Qamar Badu; Auli Irfah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to determine the effect of implementing an Articulate Storyline-assisted learning model on students’ mathematical reasoning abilities at SMP Negeri 1 Bone. Mathematical reasoning ability is an important aspect of mathematics learning that needs to be developed to help students understand, analyze, and solve mathematical problems logically. This research employed a quasi-experimental method using a post-test only control group design. The population consisted of all seventh-grade students at SMP Negeri 1 Bone, with Class VII A serving as the control group and Class VII B as the experimental group. The experimental group was taught using the Numbered Heads Together (NHT) cooperative learning model assisted by Articulate Storyline media, while the control group received instruction through the NHT cooperative learning model assisted by PowerPoint (PPT). Data were analyzed using an independent samples t-test. The results showed a significance value of 0.022 (< 0.05), indicating that H₀ was rejected. These findings suggest that the implementation of the Articulate Storyline-assisted learning model significantly affected students’ mathematical reasoning abilities. Furthermore, the effect size calculated using Cohen’s d was 0.748, indicating a large effect. Therefore, Articulate Storyline media can be considered an effective alternative for supporting mathematics learning.